The Use of Intraoperative Peripheral Extracorporeal Membrane Oxygenation in High-Risk Airways Tumor Removal Procedures in Neonates and Children: A Single-Center Case Series. Issue 10 (1st February 2021) - Huard, Donatien; Chenouard, Alexis; Fernandez, Modesto; Boyer, Julie; Guinot, Audrey; DE Napoli-cocci, Stephan; Maminirina, Pierre; Bourgoin, Pierre
Abstract : Airway surgery involving trachea or main stem bronchi in neonates and children is challenging. The use of extracorporeal support for such unusual indications is poorly described. Here, we report on three patients receiving peripheral extracorporeal membrane oxygenation (ECMO) to maintain adequate ventilation while improving surgical site exposure. Case 1 is a 9-year-old boy diagnosed with proximal left stem bronchus endoluminal tumor; cases 2 and 3 are a neonate and a young infant diagnosed with a subcarinal bronchogenic cyst. Planned ECMO use consisted in peripheral venoarterial cannulation through jugular and carotid access. There was no bleeding complication during and after surgical care. Hemodynamic and respiratory supports were optimized in all cases. Children were successfully weaned off ECMO immediately after surgery. Planned peripheral ECMO cannulation offers optimal conditions for high-risk airway surgery in neonates and children.